Children's Home Numeracy Environment Predicts Growth of their Early Mathematical Skills in Kindergarten. Issue 5 (21st January 2020) - Susperreguy, María Inés; Di Lonardo Burr, Sabrina; Xu, Chang; Douglas, Heather; LeFevre, Jo‐Anne
Abstract : This study investigated the longitudinal associations between children's early mathematics and their home numeracy environment (HNE). Chilean children from families who varied widely in socioeconomic status were assessed at the beginning and end of prekindergarten in 2016 ( N  = 419, M age  = 4:7 [years:months]), and at the end of kindergarten in 2017 ( N  = 368, M age  = 5:10). Children whose parents provided frequent operational numeracy activities (e.g., learning simple sums) at prekindergarten showed better arithmetic performance and growth in nonsymbolic and symbolic number comparison at the end of kindergarten. Parents' knowledge of number‐related games predicted children's arithmetic skills and growth in nonsymbolic number comparison. These findings underscore the persistent relations between the HNE and the development of children's mathematical skills.